The Role of Histone Deacetylase and Histone Deacetylase Inhibitors in Rheumatoid Arthritis - Rina Kriswiastiny; Radiyati Umi Partan; Hermansyah; Surya Darma; Muhammad Reagan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Rheumatoid Arthritis or RA disease is a chronic inflammatory and systemic disease associated with broad synovitis resulting in erosion of the articular cartilage and marginal bone causing joint damage. RA is an autoimmune disease with the discovery of an autoantibody, namely rheumatoid factor. The relevant antibody is anti-citrullinated protein (ACPA) antibody. Citullination on the introduction of several proteins such as fibrin, vimentin, fibronectin, collagen type II, which is expressed in the synovial membrane during inflammation by ACPA. In a recent study increased HDAC activity in the synovial tissue of RA patients has increased. Histone deacetylase or abbreviated as HDAC is an enzyme that is important in regulating gene transcription by altering the acetylation of histone proteins which results in an important regulation of repression in the implementation of inflammation. HDAC enzyme inhibitor (HDACi) is an HDAC enzyme inhibitor that can provide benefits for the treatment of various diseases including malignancy and inflammation. In inflammatory disease HDACi overcomes inflammatory cytokines such as TNF-α, IL-6 and IL-1β. One of the HDAC classes is HDAC1 which is highly expressed in the synovial fibroblasts of RA patients. HDACi can burden swollen joints, reduce mononuclear cell infiltration, request pannus orders, inhibit bone and cartilage damage.